Agama dan Altruisme: Studi Analisis Pengaruh Religiusitas Komunitas Posko Bersama Relawan dalam Aksi Kemanusiaan di Surabaya - KS, Mizro’atul Ayzahroh; Azisi, Ali Mursyid (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
This study aims to examine the relationship between religion and altruism, namely the relationship between the religious attitudes of members of the Posko community and volunteers throughout the city of Surabaya in helping the community. Attitudes possessed by every human being must be different, not a few humans who have a voluntary attitude, are generous, like to help and have a human spirit. As a volunteer who helps in a particular service or organization without wanting or involving money in return for his work. The research method in this article uses a descriptive qualitative analysis approach. By using the literature, observation and interviews are the main components of the preparation of this research. With the attitude of religiosity, volunteers are increasingly convinced that what they are doing is good and God likes good things. Because it is a form of attention that someone has with the aim of increasing helping others without being selfish. Volunteer actions are closely related to religious elements and altruism as human nature, so the urge to take part in humanitarian action grows by itself. The results showed that there was a positive relationship between the religiosity and altruism of the posko community members and volunteers throughout the city of Surabaya in their contribution to helping the community, which means that the higher the religiosity the higher the human spirit, religiosity contributes effectively to the attitudes of community members.